Long-term treatment of depression with antidepressants: a systematic narrative review. - Furukawa, T; Cipriani, A; Barbui, C; Geddes, J (2007)
OBJECTIVE: To examine the available scientific evidence for answers to clinically relevant questions on the effectiveness and tolerability of antidepressant drugs (ADs) for the long-term treatment of depression. METHOD: The Cochrane Library was searched up to July 2006. When no complete Cochrane review was available, we looked in PubMed for relevant systematic reviews or individual randomized controlled trials. RESULTS: There was no good evidence that increasing the dosage of the initial AD is an effective strategy for patients with no, or partial, response to acute-phase treatment. There was no good evidence that switching between chemical classes of antidepressant was more effective than switching within a class. There was limited support from randomized trials for several augmentation strategies. There was good evidence for the effectiveness of long-term therapy to prevent relapse in patients who remitted after acute-phase treatment. The application of principles of evidence-based medicine suggested that thoughtful, individualized application of evidence is more appropriate than general statements. CONCLUSIONS: Available evidence provides some support for the effectiveness of several augmentation strategies in the management of patients with no, or partial, response to acute-phase treatment and for the individualized application of groupwise robust evidence for maintenance treatment with ADs to prevent relapses. However, side effects of these long-term treatments with ADs are poorly studied and reported.